Targeting Nuclear Factor-Kappa B to Overcome Resistance to Chemotherapy - Godwin, Peter; Baird, Anne-Marie; Heavey, Susan; Barr, Martin; O'Byrne, Kenneth; Gately, Kathy A. (Frontiers in Oncology, 2013)
Intrinsic or acquired resistance to chemotherapeutic agents is a common phenomenon and a major challenge to the treatment of cancer patients, especially those with progressive disease. Chemoresistance is defined by a complex network of factors including multi-drug resistance proteins, reduced cellular uptake of the drug, enhanced DNA repair, intracellular drug inactivation and evasion of apoptosis. Preclinical models have demonstrated activation of the NF-κB pathway by several chemotherapy drugs, including platinum based agents, anthracyclines and taxanes. NF-κB is a key transcription factor, playing a role in the development and progression of cancer as well as chemoresistance through the activation of anti-apoptotic genes. Consequently, NF-κB has emerged as a promising anticancer target. Here, we describe the role of NF-κB in the cancer cell and in resistance to chemotherapeutic agents, particularly cisplatin. Additionally, the potential benefits and disadvantages of targeting NF-κB signalling by pharmacological intervention will be addressed.